Stock Market Development and Economic Growth in Sri Lanka (Global Journal of Management and Business Research, 2015)
Stock markets have long played an important role in economic life (Stijn, V. N., Frans, B., Ludo,
Keywords: economic growth; market capitalization; granger causality